The Influence of Increasing Concentrations of AMPD on the Efficacy of Its Penetration into a Model Skin Sebum Layer - Agnieszka Kostrzębska; Witold Musiał (MDPI AG, 2020)
Alcoholamines are widely used as auxiliary substances in various topical preparations. Their impact on the components of skin sebum allows them to be used in preparations that cleanse the skin of sebum in hair follicles. We measured the effects of various concentrations of aqueous solutions of AMPD (2-amino-2-methyl-1,3-propanediol) on model skin sebum. The volume of reacted sebum was calculated using two methods: optical assessment of the interaction of alcoholamines with the components of model skin sebum and determination of the reacted volume of model skin sebum based on the measurements of changes in the pH of the AMPD solutions. Both methods showed that the most favorable AMPD concentration for model sebum penetration was approximately 1-2%. Lower values of alcoholamine caused premature exhaustion from the solution. Excessively high concentrations resulted in the formation of a dense layer of products hindering effective skin cleansing.